Social organizations and community service delivery in China - Bingqin Li; Lijie Fang (United Nations Research Institute for Social Development (UNRISD), 2018)
This paper examines the primary social changes in China that posed major challenges to its social service delivery and the government responses to these challenges. It argues that introducing social organizations into the social service delivery system unavoidably departs from the previous narrative of the state-SO relationship by turning communities into a space that offers opportunities for each stakeholder to seek new sources of funding, new businesses and new opportunities to engage with the civil society. This is followed by a discussion of the research methods to be used in the whole research (including the three reports). The research findings provide the state of SOs in China and how different types of SOs operate to fulfil different roles.
Keywords: 330